AN ORPHAN PHENOTYPE OF CARDIOGENITAL LAMINOPATHY — MALOUF SYNDROME - T. G. Vaykhanskaya; L. N. Sivitskaya; N. G. Danilenko; T. V. Kurushko; O. G. Nizhnikova; O. G. Davydenko (Российский кардиологический журнал)
Recent decades significantly increased the spectrum of monogenic diseases associated with mutations in the gene of lamin A/C (LMNA), that codes the proteins group performing important functions in the nucleus. This pathology presents with diverse systemic tissue involvement. Mutations of the gene LMNA are the cause of more than ten different inherited disorders — laminopathies. In clinical practice, there are cardial phenotypes common, i. e. dilation cardiomyopathy (DCMP), skeletal-muscular dystrophies (Emery-Dreifuss dystrophy, inherited and limbleveled) and more rare forms — lipodystrophies, progeroid phenotypes (acromandibular dysplasia, Hutchinson-Gilford progeria, atypical Werner syndrome), Malouf syndrome. Malouf syndrome, known nowadays as cardiogenital syndrome, is rare inborn pathology with DCMP phenotype and ovarial dysgenesis (females) or primary testicular failure (males), with cognitive delay and variety of skeletal abnormalities (usually facial dysmorphism and marfanoid signs). The arcticle presents a clinical case of female patient with primary amenorrhea, hypogonadism, DCMP, cognitive deficiency, hypodeveloped secondary gender signs, body mass deficiency, and facial dysmorphism. Radiation, viral parotitis, autoimmunity and Turner syndrome were ruled out. Signs if bone dysplasia typical for mandibular-acral dysplasia are absent. Relatives of the 1st line are normal. With sequencing method, we searched for mutations in the gene LMNA, but there were no mutations. Results make it to suggest that pathogenetic mechanisms of Malouf syndrome are not only of “lamin” nature but of other genetic causes too. The article also points on the key issues of diagnostics and treatment, presents differential criteria and clinical signs of an orphan disease.